Cultural Heritage, Sustainable Development and Inclusive Growth: Global Lessons for the Local Communities Under a Marketing Approach - Vegheș, Călin (European Journal of Sustainable Development, 2018)
Seen often like something from the past, bearing a certain, not always clear, significance and probably having a particular value, cultural heritage, in its tangible and intangible forms, is far from being considered an asset that local communities may benefit from. Therefore, the contribution of the cultural heritage to the sustainable development of the local communities is less relevant and expresses accurately the extent toward which individuals and institutions understand, value, care for and enjoy this heritage. Widening of the economic and social inequalities in many of the advanced and emerging economies led toward a different model of growth and development addressing and including the entire community aiming not only to improve the economic performance in terms of the gross domestic product, but also the standards of living of its members in terms of income, employment and overall quality of life. Paper presents the results of an exploratory assessment of the connections between the key indicators describing cultural heritage, sustainable development and inclusive growth, under a vision of marketing, in order to identify potential paths local communities may follow by learning the global lessons on how cultural heritage may support the sustainable development in order to ensure their inclusive growth. Keywords: Cultural heritage, sustainable development, inclusive growth, local communities, marketing